Implementation of Profile Matching and Linear Interpolation Methods for Web-Based Employee Selection System of PT Berdikari Meubel Nusantara - Wahyu Wibowo, Dimas; Retno Tri Hariati Ririd, Ariadi; Septian Jaya, Ariono (UPT P2M State Polytechnic of Malang, 2024)
Recruiting employees by means of good selection can show the company's expertise to get competent candidates to support the company's performance well. Employee recruitment at PT BERDIKARI MEUBEL NUSANTARA was done manually and produced subjective decisions when the ability of prospective employees was not too different.To overcome these problems,this research was made to assist recruiters (HRD) in selecting and choosing prospective employees according to company needs, therefore researchers created a Decision Support System (DSS).Decision Support System (DSS) uses the Profile Matching and Linear Interpolation method, so that the method can work well it requires several criteria for prospective employees and is able to provide alternative recommendations and in accordance with the company's needs.The results of the research on the application of the Profile Matching method with Linear Interpolation can assist users in providing recommendations for prospective employees according to what the company expects, the value of the core factors and secondary factors greatly affect the results of accuracy because both are used in the assessment, it will be recommended the results of the total score and sorted b who gets the highest total score.This application is considered effective by obtaining User Acceptance Testing of 99.33% and this decision support system can help companies in selecting employees according to company needs.